Anterior cervical discectomy and fusion with self-locking standalone cage for the treatment of cervical degenerative disc disease in patients over 80 years - Jian Zhou; An’nan Hu; Xiaogang Zhou; Jian Dong (Journal of Orthopaedics and Traumatology)
Abstract Background The need for anterior cervical discectomy and fusion (ACDF) for cervical degenerative disc disease (CDDD) will probably grow dramatically in the geriatric population. However, ACDF with self-locking standalone cages in patients over 80 years has not yet been investigated. This study aimed to assess the clinical and radiographic results in patients over 80 years treated by ACDF with self-locking standalone cages. Methods Between January 2018 and December 2019, patients with CDDD treated with ACDF were retrospectively stratified into two groups: the older group (≥ 80 years) and the younger group (< 65 years). The data collected included the demographics, preoperative comorbidities, intraoperative parameters, length of hospital stay, complications, clinical scores, and radiological parameters. Results A total of 123 patients were included in the study. The mean follow-up duration was 28.3 ± 2.4 months. The hospital stay was 5.3 ± 0.6 days and 3.8 ± 0.4 days, respectively, for the older and younger groups. Postoperative complication rate was found higher in the older group than that of the young group without significance. All the patient-reported outcome parameters had significant improvement at the final follow-up. The two groups had no significant differences in terms of the excellent and reasonable rates, fusion rate, and the C2–C7 Cobb angle. Conclusions Although a slightly higher incidence of complications, poorer recovery rate, and more extended hospital stay were found, without significant differences, satisfactory clinical and radiographic results were obtained in the older patients. The self-locking standalone cage is a safe and viable option for patients over 80 years who suffer from CDDD. Level of evidence Level IV.